2021
DOI: 10.5433/1679-0359.2021v42n5p2751
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of salt stress on the physiology and production of bell peppers by treatment with salicylic acid

Abstract: The use of saline water for irrigation in semi-arid regions has become a reality due to the water scarcity that occurs in most of the year. In this scenario, exogenous application of salicylic acid may be a strategy to mitigate the deleterious effects of salt stress on plants and ensure the production of socioeconomically important crops in the semiarid region of Northeast Brazil, such as bell pepper. Thus, this study examines the osmoprotective effect of salicylic acid on gas exchanges, chloroplast pigments a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…The high concentration of salts in irrigation water can result in osmotic and ionic imbalance, due to the excess of Na + and Clions, affecting the availability and absorption of water and nutrients by plants (YAISH et al, 2016;SAMADDAR et al, 2019). Symptoms observed in plants under salt stress include delay in leaf production, necrosis of shoots and roots, and reduction of leaf area and photosynthetic activity, thus affecting their growth (VELOSO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The high concentration of salts in irrigation water can result in osmotic and ionic imbalance, due to the excess of Na + and Clions, affecting the availability and absorption of water and nutrients by plants (YAISH et al, 2016;SAMADDAR et al, 2019). Symptoms observed in plants under salt stress include delay in leaf production, necrosis of shoots and roots, and reduction of leaf area and photosynthetic activity, thus affecting their growth (VELOSO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Preharvest applications of SA have stimulated the disease resistance against fungal infection of pepper fruits [19][20][21][22]; accordingly, it also reduced the decay incidence and postharvest losses during storage. In the scientific literature, studies focusing on the action of SA preharvest application on salinity stress oxidative damage of sweet pepper plants are also incipient [2,23,24]. Nevertheless, few studies have investigated the effect of SA preharvest treatment on increasing crop yield and quality of pepper fruit [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…close their stomata as a defense mechanism, aiming at reducing the loss of water to the atmosphere and reducing the absorption of toxic ions (Lima et al, 2019). Veloso et al (2021), evaluating the osmoprotective capacity of salicylic acid on 'All Big' bell pepper plants irrigated with waters of different salinity levels, found that the highest value of gs (0.27 mol H 2 O m -2 s -1 ) was obtained in plants subjected to SA concentration of 1.5 mM, with reductions from this concentration. 'Gaúcho' melon plants (Figure 2B) subjected to nutrient solution electrical conductivity of 2.1 dS m -1 and without application of salicylic acid (0 mM) obtained the highest leaf transpiration (5.52 mmol H 2 O m -2 s -1 ).…”
Section: Resultsmentioning
confidence: 99%